The vampire inside my camera: an exhumation of gender, monstrosity and queer worldmaking through photography and video - Carosin, Gem (Michaelis School of Fine Art, 2025)
Gem Carosin's MFA project The Vampire inside my Camera: an exhumation of gender, monstrosity and queer worldmaking through photography and video uses the vampire character as metaphor investigating shame and desire through a queer lens. Examining how the vampire has taken shape in the public imagination, this text discusses folktales, art- historical and literary influences. Through a historical revisionist approach, monstrosity and the example of the vampire are parallelled to the negative assumptions about queer lives. By recontextualising the compositions and lighting of paintings, Gem draws the past into the present. Temporality, chronopolitics and the disruptive capacity of the undead immortal are of interest to Gem as they explore the limits of heteronormative structures of time-keeping. They break down how and why queer people may use troubled temporality and fluid depictions of gender to imagine utopian futures and queer worlds. This is pinpointed in the horror genre of film and various contemporary artforms that displace linearity. Gem's photography and video art portrays them as the monstrous vampire character, positioning their project as specific to them and their orientation to the world. Using their queer chosen family as photographic subjects, Gem explores what it means to be a monster among monsters in a safe-haven of eternal night. This body of work emphasises the importance of storytelling and imagining in creating queer spaces. Prioritising humour, joy and pleasure in their video work highlights how queer history is often defined by queer suffering. Gem hopes that their photographs will reach other queer individuals and provide comfort and kinship.